Non-indigenous People (non-pribumi) and the Indonesian Legal System - Winarta, Frans Hendra (Pelita Harapan University, 2003)
Everyone, especially indigenous people, has a particularly strong claim under the Universal Declaration of Human Rights to keep his own cultural traditions. Article 27 paragraph (I) of Universal Declaration of Human Rights. Indigenous people have been regarded as an emerging object of international law, although it may be more logical to regard them as one class of minority group which has a particularly strong claim for fair treatment from a nation state with a majority of settler descendants. Indonesia has no specific definition of indigenous people; however, it regards its citizens as either Â indigenous or non-indigenous people. It is a debated issue that the group of ethnic Chinese, as a minority group of non-indigenous people in Indonesia, are often treated unfairly compared to the indigenous people. This paper will briefly explain how the ethnic Chinese struggle for their basic rights in Indonesia. Furthermore, it will discuss the specific laws and regulations intended to have the effect of creating of perpetuating racial discrimination and what the impact of these are on the process of Indonesian nation building. Finally, the writer draws some conclusions.Â